La posta elettronica Uno strumento utile in ambito sanitario - Conti, Antonio (Proceedings e report, 2005)
E-mail is becoming more and more an essential tool for the correct transfer of information, which represents the sine qua non for the provision of effective and efficient health services to citizens. This manual introduces the conscious use of this interaction channel and the guidelines produced by the main international medical-scientific organisations, with the aim of offering an aid for the appropriate use of new ways of interacting between doctor and patient.